Mapping the problems in using the rural library services among rural youth in Malaysia - Mazuki, Raidah; Omar, Siti Zobidah; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Bolong, Jusang (WorldConferences.net, 2014)
Rural Library plays an important role in creating a knowledgeable society. The implementation of rural library since the year 2000 is in line with the Malaysian government aspiration and is embedded in Vision 2020. Albeit, its long years of establishment, however, yet, not much is known on the issues pertaining to rural library particularly with regard to the problem faced by the user in using the rural library services. Thus, the main attempt of this study is to identify the problems faced by the rural youth in using the rural library services. This is quantitative study where through a multi stage cluster random sampling, a total of 400 rural youth from 16 rural libraries were selected as the respondents. The analyses performed have confirmed that the top three problems faced by rural youth in using the rural library services were lacking of promotion, inadequate building spaces and too many children visiting the rural library. A number of discussions have been highlighted and it is a hope that it can assist the relevant parties in constructing concrete strategies to further develop the rural library in Malaysia.